PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS LEARNING CYCLE 5E MATERI ENZIM UNTUK SMA DALAM MELATIH KETERAMPILAN BERPIKIR KRITIS - ERMI SUGIHARTI BM (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Learning on any material enzyme will add understanding siswa if in study done through an investigation related roles and work, therefore needed learning cycle 5E based student worksheet, which in the process of learning involving student critical thingking. This research was intended to know feasibility of learning cycle 5E based student worksheet that can facilitate student critical thingking. This research is the development of student worksheet using 4D models which only up whit the phase develop ( development ). The parameters measured were the feasibility by 2 lecturer and 1 teachers biology. The results of research that has been done shows that the developed viable LKS with percentage feasibility of 82,15% with criteria worthy Key word: Student worksheet, Learning cycle 5E, Critical thinking, Enzymes